Genetic Features and TP53 Mutations in Chronic Lymphocytic Leukemia - Erdoğan Özünal, Işıl; Elverdi, Tuğrul; Salihoğlu, Ayşe; Eşkazan, Ahmet Emre; Ar, Muhlis Cem; Öngören, Şeniz; Başlar, Zafer; Aydın, Yıldız; Hatırnaz, Özden; Sayitoğlu, Müge; et al. (Cerrahpaşa Medical Journal, 2021)
Objective: In this study, we aimed to evaluate the incidence and type of tumor protein 53 mutations and compare this with 17p deletion and other prognostic factors in 50 outpatient patients who were diagnosed with chronic lymphocytic leukemia between 2001 and 2013 in our hematology outpatient clinic. Methods: In the study, 10 cc of blood was collected from patients and variations in the 4-11 exons of the tumor protein 53 gene in the cDNAs were determined by polymerase chain reaction and Sanger sequence analysis methods. Demographic data as age, sex, time of diagnosis, time interval between diagnosis and treatment, disease stage, 17p deletion status, zeta-associated-protein kinase 70 and CD38 positivity were obtained retrospectively from outpatient files. Results: Twenty-eight patients (56%) were male. Age interval was between 36 and 68 years. 17p deletion analyzed by fluorescence in situ hybridization was positive in 7 patients (14%) and negative in 43 patients (86%). Tumor protein 53 mutations could be analyzed in 17 patients; 5 patients were wild type, and all of the remaining 12 patients had a cytosine (C) to guaine base (G) alteration at position 215. This alteration was considered as a single nucleotide polymorphism. In 9 of the patients with mutations in the tumor protein 53 gene, 17p deletion was negative. Conclusion: Current treatment guidelines recommend screening for 17p deletion in chronic lymphocytic leukemia patients, but do not include screening for tumor protein 53 mutations. In our study group, tumor protein 53 gene polymorphism which has been associated with poor prognosis and drug resistance in the literature was detected in 12 (70.5%) of 17 patients. Since 9 of the patients (75%) with tumor protein 53 gene polymorphism were found to be 17p deletion negative, in addition to 17p deletion, the analysis of tumor protein 53 gene mutations can be recommended, at least before planning the treatment or before changing the treatment regimen in poor responsive patients. Cite this article as: Erdoğan Özünal I, Elverdi T, Salihoğlu A, et al. Genetic features and TP53 mutations in chronic lymphocytic leukemia. Cerrahpaşa Med J. 2021;45(3):221-226.